Mulberry leaf aqueous extract ameliorates blood glucose and enhances energy expenditure in obese C57BL/6J mice. (December 2019) - He, Xiaoyun; Li, Haoyu; Gao, Ruxin; Zhang, Chuanhai; Liang, Fei; Sheng, Yao; Zheng, Shujuan; Xu, Jia; Xu, Wentao; Huang, Kunlun
Graphical abstract: Highlights: Treatment with mulberry leaf aqueous extract (MLAE) decreased blood glucose in diet induce obese (DIO) mice. Treatment with MLAE improved the energy expenditure in DIO mice. MLAE have no toxicological effects on liver and kidney of DIO mice. Treatment with MLAE restored gut microbiota imbalance in DIO mice. Abstract: Mulberry leaf garners much attention from researchers because of its hypoglycemic effect. This study's objective was to determine the impact of mulberry leaf aqueous extract (MLAE) on decreasing blood glucose and promoting energy expenditure in obese C57BL/6J mice (induced by a high-fat diet). The mice were fed with high fat diet and treated with MLAE for 12 weeks. The results showed that MLAE significantly ameliorated the hyperglycemia and insulin resistance in mice that were induced by their high-fat diet. The improved blood glucose metabolism accompanied by elevated energy expenditure was found. Abundant flavonoids, polyphenols, and alkaloids in MLAE may have contributed to the above results. Also, MLAE restored gut microbiota imbalance in obese mice and was beneficial to their liver and kidney functioning. Together, these results suggest MLAE may be a potent ingredient in dietetics and can serve as a safe hypoglycemic ingredient in health product development.